The prognostic value of the cytological composition of the tear in the diagnosis of endometriosis - Y. A. Huseva; O. L. Zharikova; A. V. Vasilevskaya (Российский офтальмологический журнал)
Purpose. To investigate the cell composition of the tear in healthy women and endometriosis patients in order to find the potential diagnostic criteria of endometriosis. Material and methods. Tear samples obtained from the lower fornix of the conjunctiva using a glass capillary tube were microscopically examined in 100 females aged 18 to 48: 60 healthy women, who made up the control group, and 40 patients with endometriosis. Results. The share of women with endometriosis who were found to have erythrocytes was 32.5 %, which was significantly higher as compared with the control group, where it was 25.0%. 69.2 % of women with endometriosis showed haemolacria in the follicular phase of the menstrual cycle, which significantly exceeded the percentage of women with erythrocytes in the tear (30.8 %) who had them in the luteal phase. Epitheliocytes were found in the tear of 97.5 % of patients with endometriosis, versus 75.0 % of healthy women. In all 100 % of such patients, these cells were found in the follicular phase of the menstrual cycle, compared with 74.3 % of healthy women who showed these cells in the same phase of the cycle. The share of women with endometriosis showing the ++ quantity of epitheliocytes in the tear was 56.4 %, which was significantly higher than the 20 % of the control group subject with the same level of epitheliocytes. It is to be noted that group accumulations of epitheliocytes were found in 15 % of endometriotic patients, which was significantly higher than in healthy women, of whom only 8.3 % had such accumulations. 90 % of endometriosis group cases revealed glandular cuboidal epithelial cells in the tear, which morphologically resembling endometrial cells. Conclusion. The revealed properties of the cytological composition of the tear of patients with endometriosis reflected particular links in its etiopathogenesis, which suggests that the study of tear parameters can help predict the incidence of the "endometrioid disease" and develop pathogenetically oriented treatment methods.